Nano composite chain extender based on in-situ polymerization modification as well as preparation method and application of nano composite chain extender

Through the in-situ polymerization modified nanocomposite chain extender and titanate coupling agent, the molecular chain break of PET is repaired, the mechanical properties of PET are improved, and the problem of performance deterioration after PET is solved, and the application of efficient regenerated materials is realized.

CN120349456APending Publication Date: 2025-07-22ZHEJIANG ALICE DYEING & FINISHING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510687941.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-27
Publication Date
2025-07-22

AI Technical Summary

Technical Problem

The prior art is difficult to effectively repair PET molecular chain breakage, resulting in significant deterioration in mechanical properties of PET materials after multiple recycling, limiting the recycling and reuse of PET.

Method used

Using a nanocomposite chain extender based on in-situ polymerization modification, the PET molecular chain is repaired through a polymer composed of nanosilica with the putaway structure, glycidyl methacrylate, hydroxyethyl acrylate and disulfide bond crosslinking agent, and the nanoparticle dispersion is optimized through the titanate coupling agent to form a strong interface bond.

Benefits of technology

It significantly improves the mechanical properties of recycled PET, makes its intrinsic viscosity and tensile strength close to or reach the native PET level, improves processing performance, and is suitable for high value-added products such as precision injection molded parts and industrial fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120349456A_ABST
    Figure CN120349456A_ABST
Patent Text Reader

Abstract

The invention provides a nano-composite chain extender based on in-situ polymerization modification as well as a preparation method and application of the nano-composite chain extender. The nano-composite chain extender has a shell-core structure, a shell layer is modified silicon dioxide, and a core layer is a polymer composed of glycidyl methacrylate, hydroxyethyl acrylate and a disulfide bond cross-linking agent. The preparation method comprises the following steps: mixing the prepared nano-composite chain extender with recycled PET fragments, then adding a titanate coupling agent, carrying out shear blending through a twin-screw extruder, and carrying out water-cooling pelletizing on extruded material strips, so as to obtain the composite material, through the synergistic effect of the nano-composite chain extender and the titanate coupling agent, the intrinsic viscosity and mechanical properties of the composite material are remarkably enhanced; the method can be directly used for high-added-value products such as precise injection molding parts and industrial fibers, and the problem that raw materials are degraded and used in traditional recycling is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of waste PET recycling and utilization, and specifically provides a nano-composite chain extender based on in-situ polymerization modification, its preparation method and application. Background Art

[0002] Polyethylene terephthalate (PET), as the thermoplastic polyester material with the largest global production volume, is widely used in fields such as packaging, textiles, electronics, and the automotive industry due to its excellent mechanical properties, transparency, chemical resistance, and processability. However, during multiple melt processing or environmental exposure, PET materials are prone to thermal oxidative degradation and hydrolysis reactions, resulting in molecular chain breakage, decreased molecular weight, and increased end carboxyl group content, leading to significant deterioration of the mechanical properties and processing performance of the materials. Therefore, it severely restricts the recycling and reuse of PET.

[0003] Currently, only about 30% of PET waste globally is recycled through mechanical recycling to achieve closed-loop utilization. Traditional mechanical recycling technologies mainly achieve physical regeneration through melt extrusion, but they cannot repair the chemical damage of molecular chains. Research shows that after three recycling cycles, the intrinsic viscosity of PET will drop from the initial 0.8 dL / g to below 0.4 dL / g, and the tensile strength loss exceeds 40%. Although chemical recycling methods (such as depolymerization-repolymerization) can theoretically achieve complete repair of the molecular structure, they face problems such as high loss, complex process control, and catalyst residue, and their economic efficiency and large-scale application are restricted. Therefore, developing efficient physical-chemical synergistic technologies to achieve the performance regeneration of rPET through molecular structure reconstruction has become a key research direction to break through the performance bottleneck of recycled materials. Summary of the Invention

[0004] (I) Technical Problems to be Solved

[0005] In view of the deficiencies of the prior art, the present invention provides a nano-composite chain extender based on in-situ polymerization modification, its preparation method and application, and solves the problems raised in the above background art.

[0006] (II) Technical Solutions

[0007] To achieve the above objectives, the present invention is realized through the following technical solutions:

[0008] According to the first aspect of the present invention, there is provided a nano-composite chain extender based on in-situ polymerization modification, and the nano-composite chain extender has a core-shell structure, wherein the shell layer is modified silica, and the core layer is a polymer composed of glycidyl methacrylate, 2-hydroxyethyl acrylate, and a disulfide cross-linking agent.

[0009] Preferably, the modified silica is nano-silica grafted with 2-cyanophenyl 2-dithiobenzoate.

[0010] Preferably, the particle size of the nano-composite chain extender is 30 to 80 nm, and the thickness of the shell layer is 10 to 30 nm.

[0011] According to the second aspect of the present invention, a preparation method of a nano-composite chain extender based on in-situ polymerization modification is provided, including the following steps:

[0012] S1. Vacuum dehydrate the nano-silica, then disperse the dehydrated nano-silica in anhydrous toluene, add a silane coupling agent and 2-cyanophenyl 2-dithiobenzoate, and react under a nitrogen atmosphere to obtain modified silica;

[0013] S2. Mix glycidyl methacrylate, 2-hydroxyethyl acrylate and dithiodibenzoic acid, then add the modified silica, carry out an in-situ polymerization reaction under ultraviolet light irradiation, and then sequentially carry out centrifugal washing with acetone and deionized water, and vacuum dry to obtain the nano-composite chain extender.

[0014] Preferably, in step S1, the mass ratio of the nano-silica to the anhydrous toluene is 1:2 to 5;

[0015] The particle size of the nano-silica is 20 to 50 nm;

[0016] The mass ratio of the nano-silica to the silane coupling agent and 2-cyanophenyl 2-dithiobenzoate is 100:10:10 to 20.

[0017] Preferably, the silane coupling agent is selected as KH-570.

[0018] Preferably, in step S1, the temperature of the vacuum dehydration is 140 to 160 °C, and the time is 2 to 3 h;

[0019] The temperature of the reaction is 60 to 80 °C, and the time is 5 to 8 h.

[0020] Preferably, in step S2, the mass ratio of the modified silica, glycidyl methacrylate, 2-hydroxyethyl acrylate and dithiodibenzoic acid is 100:10 to 15:8 to 12:3 to 5.

[0021] Preferably, in step S2, the intensity of the ultraviolet light is 10 to 15 mW / cm 2 ;

[0022] The temperature of the in-situ polymerization reaction is 40 to 60 °C, and the time is 2 to 8 h;

[0023] The temperature of the vacuum drying is 50 to 60 °C, and the time is 12 to 24 h.

[0024] According to the third aspect of the present invention, a method for preparing a composite material based on recycled PET is provided. The nano-composite chain extender is mixed with recycled PET fragments, and then a titanate coupling agent is added. Shear blending is carried out by a twin-screw extruder, and the extruded strip is cooled and pelletized with water to obtain the composite material;

[0025] Among them, the nano-composite chain extender is selected from the above-mentioned nano-composite chain extender or the nano-composite chain extender obtained according to the above preparation method.

[0026] Preferably, the mass ratio of the recycled PET fragments, the nano-composite chain extender, and the titanate coupling agent is 100:1 to 2:0.1 to 0.3;

[0027] The titanate coupling agent is selected from at least one of NDZ-401, OL-T951, and TMC-101;

[0028] The condition parameters of the shear blending are: the heating temperature is 240 to 270 °C, and the screw speed is 200 to 500 rpm.

[0029] The nano-composite chain extender prepared by the present invention has epoxy groups, which chemically react with the carboxyl or hydroxyl groups at the ends of the PET molecular chains. By generating new ester bonds or ether bridges to break the chain segments, the degree of polymerization is increased, and the repair and extension of the molecular chains are realized. Nano-silica, as a physical cross-linking node, strengthens the interaction between PET chains through hydrogen bonds / van der Waals forces to construct a three-dimensional nano-enhanced network structure. The titanate coupling agent chemically grafts and modifies the surface of the nanoparticles to inhibit their agglomeration tendency and ensure the nano-scale dispersion of the nanoparticles in the PET matrix. Through the synergistic effect of the nano-composite chain extender and the titanate coupling agent, the extended main chain of the nano-composite chain extender provides more binding sites for the nanoparticles, and the optimized dispersion state of the titanate coupling agent enhances the interfacial binding energy between PET and the nanoparticles, forming a strong interfacial binding and significantly reducing the risk of interfacial peeling caused by stress concentration.

[0030] (III) Beneficial effects

[0031] The present invention provides a nano-composite chain extender based on in-situ polymerization modification, its preparation method and application. It has the following beneficial effects:

[0032] (1) A nano - composite chain extender provided by this solution is applied to recycled PET. Through the chain - extension reaction, the molecular chain breakpoints generated by PET degradation are repaired, its molecular weight is enhanced, and the tensile strength is restored, making the material properties close to or reach the level of virgin PET, significantly improving the mechanical properties of recycled PET. The nano - composite chain extender effectively inhibits the drooling phenomenon during extrusion or injection molding by increasing the melt viscosity and improving the melt elasticity. At the same time, the nano - composite chain extender utilizes the interface slip effect to reduce the melt viscosity and balance the viscosity increase caused by chain extension, thereby improving the processing efficiency. This synergistic effect enables low - molecular - weight recycled PET to be directly used for high - value - added products such as precision injection - molded parts and industrial fibers, avoiding the problem of raw material degradation in traditional recycling.

[0033] (2) A composite material based on recycled PET provided by this solution has an intrinsic viscosity of more than 0.9 dL / g and a tensile strength of more than 60 MPa, with significantly enhanced intrinsic viscosity and mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 SEM diagram of the nano - composite chain extender prepared in Example 1 of the present invention. DETAILED DESCRIPTION OF THE INVENTION

[0035] To better illustrate and elaborate on the content of the present invention, the following is described in detail with reference to specific examples.

[0036] Example 1

[0037] A nano - composite chain extender is prepared by the following method:

[0038] S1. 50 g of silica with a particle size of 20 nm is vacuum - dehydrated at 150 °C for 3 h. The dehydrated nano - silica is dispersed in 100 g of anhydrous toluene, then 5 g of silane coupling agent KH - 570 and 5 g of 2 - cyano - 2 - phenyl dithiobenzoate are added, and the reaction is carried out at 75 °C for 6 h under a nitrogen atmosphere to obtain modified silica.

[0039] S2. After mixing 5 g of glycidyl methacrylate, 4 g of 2 - hydroxyethyl acrylate and 1.5 g of dithiodibenzoic acid, 50 g of the modified silica is added, and the in - situ polymerization reaction is carried out at 50 °C for 2 h under ultraviolet light irradiation with an intensity of 12 mW / cm 2 . Then the polymerization product is successively centrifuged and washed with acetone and deionized water, and vacuum - dried at 60 °C for 12 h to obtain the nano - composite chain extender.

[0040] The nano - composite chain extender prepared in this example is as Figure 1As shown, it has a core-shell structure, where the shell layer is nano-silica grafted with 2-cyanophenyl 2-dithiobenzoate, and the core layer is a polymer composed of glycidyl methacrylate, 2-hydroxyethyl acrylate and a disulfide cross-linking agent. The particle size of the nano composite chain extender is 30 nm, and the thickness of the shell layer is 15 nm.

[0041] Example 2

[0042] The preparation method of this example is the same as that of Example 1, except that in step S1, the mass ratio of nano-silica, silane coupling agent KH-570 and 2-cyanophenyl 2-dithiobenzoate is 100:10:20. For the nano composite chain extender prepared in this example, the particle size of the nano composite chain extender is 80 nm, and the thickness of the shell layer is 30 nm.

[0043] Example 3

[0044] The preparation method of this example is the same as that of Example 1, except that in step S2, the mass ratio of modified silica, glycidyl methacrylate, 2-hydroxyethyl acrylate and dithiodibenzoic acid is 100:15:12:5. For the nano composite chain extender prepared in this example, the particle size of the nano composite chain extender is 60 nm, and the thickness of the shell layer is 30 nm.

[0045] Application Example 1

[0046] Mix 1 kg of recycled PET fragments with 20 g of the nano composite chain extender prepared in Example 1, then add 20 g of NDZ-401, and carry out shear blending through a twin-screw extruder. After extruding the strip, cool it with water and cut it into pellets, and then injection mold it into standard test specimens. The conditions for shear blending are: the heating temperature is 240-270 °C, and the screw speed is 200-500 rpm.

[0047] Application Example 2

[0048] Mix 1 kg of recycled PET fragments with 10 g of the nano composite chain extender prepared in Example 1, then add 30 g of NDZ-401, and carry out shear blending through a twin-screw extruder. After extruding the strip, cool it with water and cut it into pellets, and then injection mold it into standard test specimens. The conditions for shear blending are the same as those in Application Example 1.

[0049] Comparative Example 1

[0050] In this comparative example, recycled PET fragments are directly processed without adding a chain extender and a coupling agent, and shear blending is carried out through a twin-screw extruder. After extruding the strip, cool it with water and cut it into pellets, and then injection mold it into standard test specimens. The conditions for shear blending are the same as those in Application Example 1.

[0051] Comparative Example 2

[0052] Using unmodified nano-silica to replace the modified silica in Example 1 to prepare a chain extender, mixing it with recycled PET fragments, adding NDZ-401, and performing shear blending through a twin-screw extruder. After extruding the strand, it is cooled and pelletized by water, and then injection molded into standard test specimens. The shear blending conditions are the same as those in Application Example 1.

[0053] Comparative Example 3

[0054] Mix 1 kg of recycled PET fragments, 10 g of commercially available epoxy-based chain extender ADR-4368, and then add 10 g of NDZ-401, and perform shear blending through a twin-screw extruder. After extruding the strand, it is cooled and pelletized by water, and then injection molded into standard test specimens. The shear blending conditions are the same as those in Application Example 1.

[0055] Perform intrinsic viscosity and tensile strength tests on the test specimens prepared in Application Examples 1 and 2 of the present invention, and Comparative Examples 1 to 3, as shown in Table 1.

[0056] Table 1

[0057] Test spline Tensile strength (MPa) Intrinsic viscosity (dL / g) Application Example 1 62 0.98 Application Example 2 66 0.92 Comparative Example 1 42 0.34 Comparative Example 2 45 0.51 Comparative Example 3 60 0.78

[0058] It can be seen by comparison that through the prepared nano-composite chain extender, the epoxy-based chain extender is promoted to react with the end groups of PET molecular chains through chemical chain extension repair technology, the broken chain segments are repaired and the molecular weight is increased, so that the mechanical properties of the recycled PET material are restored to 90-95% of the virgin PET. Among them, the modified nano-silica acts as a cross-linking node, enhances the intermolecular force through hydrogen bonds, forms a three-dimensional network structure, realizes the physical enhancement of the composite material, and the surface of the nano-particles is modified by titanate coupling agent to achieve nano-scale dispersion and reduce interface defects. Furthermore, through the synergistic effect of the nano-composite chain extender and the titanate coupling agent, the intrinsic viscosity and mechanical properties can be significantly improved.

[0059] The composite material obtained by the present invention can not only be injection molded, but also spun and blow molded, and used as raw materials for fabrics and plastic products. Due to the improved mechanical properties and thermal stability after modification, it can be applied to fields such as daily chemical packaging bottles, films, fiber products, and engineering plastics.

[0060] Although the embodiments of the present invention have been shown and described, it will be understood by those of ordinary skill in the art that various changes, modifications, substitutions and variations can be made in these embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A nano composite chain extender based on in-situ polymerization modification, characterized in that: The nano composite chain extender has a core-shell structure, wherein the shell layer is modified silica and the core layer is a polymer composed of glycidyl methacrylate, 2-hydroxyethyl acrylate and a disulfide crosslinking agent.

2. The nano composite chain extender based on in-situ polymerization modification according to claim 1, characterized in that: The modified silica is nano silica grafted with 2-cyanophenyl dithiobenzoate.

3. The nano composite chain extender based on in-situ polymerization modification according to claim 1, wherein: The particle size of the nano composite chain extender is 30-80 nm, and the thickness of the shell layer is 10-30 nm.

4. A method for preparing the nano-composite chain extender according to any one of claims 1 to 3, characterized in that: It includes the following steps: S1. Vacuum dehydrate the nano silica, then disperse the dehydrated nano silica in anhydrous toluene, add a silane coupling agent and 2-cyanophenyl dithiobenzoate, and react under a nitrogen atmosphere to obtain modified silica; S2. Mix glycidyl methacrylate, 2-hydroxyethyl acrylate and dithiodibenzoic acid, then add the modified silica, carry out an in-situ polymerization reaction under ultraviolet light irradiation, and then sequentially carry out centrifugal washing with acetone and deionized water, and vacuum dry to obtain the nano composite chain extender.

5. The preparation method of a nano composite chain extender according to claim 4, characterized in that: In step S1, the mass ratio of the nano silica to anhydrous toluene is 1:2-5; The particle size of the nano silica is 20-50 nm; The mass ratio of the nano silica to the silane coupling agent and 2-cyanophenyl dithiobenzoate is 100:10:10-20.

6. The preparation method of a nano composite chain extender according to claim 4, characterized in that: In step S1, the temperature of the vacuum dehydration is 140-160 °C and the time is 2-3 h; The temperature of the reaction is 60-80 °C and the time is 5-8 h.

7. The preparation method of a nano composite chain extender according to claim 4, characterized in that: In step S2, the mass ratio of the modified silica, glycidyl methacrylate, 2-hydroxyethyl acrylate and dithiodibenzoic acid is 100:10-15:8-12:3-5.

8. The preparation method of a nano composite chain extender according to claim 4, characterized in that: In step S2, the intensity of the ultraviolet light is 10 to 15 mW / cm 2 ; The temperature of the in-situ polymerization reaction is 40-60 °C and the time is 2-8 h; The temperature of the vacuum drying is 50-60 °C and the time is 12-24 h.

9. A method for preparing a composite material based on recycled PET, characterized in that: Mix the nano composite chain extender with recycled PET fragments, then add a titanate coupling agent, and carry out shear blending through a twin-screw extruder, and water-cool and pelletize the extruded strip to obtain a composite material; Among them, the nano composite chain extender is selected from the nano composite chain extender described in any one of claims 1 to 3 or the nano composite chain extender obtained by the preparation method described in any one of claims 4 to 8.

10. The preparation method of a composite material based on recycled PET according to claim 9, characterized in that: The mass ratio of the recycled PET fragments, nano composite chain extender and titanate coupling agent is 100:1-2:0.1-0.3; The titanate coupling agent is selected from at least one of NDZ-401, OL-T951 and TMC-101; The condition parameters of the shear blending are: the heating temperature is 240-270 °C and the screw speed is 200-500 rpm.